Optimalisasi Komponen Pariwisata 4A: Studi Kasus Taman Wisata Alam Punti Kayu Palembang - Nurvia Nathasya; Debby Fifiyanti; Fernando Africano (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
Punti Kayu Nature Tourism Park (TWA) in Palembang is one of the natural tourism areas with great potential; however, it has experienced a decline in visitor interest. This is due to poorly maintained facilities that are no longer functional. Many supporting tourism amenities are damaged or not functional optimally, thus reducing visitors comfort. Several activities such as the animal park children’s playground, and water availability shown signs of declining quality. Therefore, more optimal management is needed to maintain ecological sustainability and enhance tourism appeal. This study aims to analyze the tourism components in the development of TWA Punti Kayu, focusing on the aspects of attraction, amanities, accessibility, and ancillary services. The method used is a qualitative approach through interviews, observations, and documentation. The research subjects include the managers of TWA Punti Kayu and visitors. The results are expected to provide a comprehensive overview of the actual conditions of the area and offer management strategy recommendations that can help optimize the natural tourism potential of TWA Punti Kayu, enabling it to compete and regain popularity.